The Sexual Behaviors Related Factors of Senior High Schools Teenagers in Bukittinggi 2017 - Nurdin, Yonrizal; Refnandes, Randy; Aulia, Isny Shafira (Indian Journal of Community Health, 2017)
Background: The increasing number of the teenager’s sexual behavior in Indonesia is influenced by many factors. The purpose of this study was to determine factors associated with sexual behavior of Senior High Schools in Bukittinggi. Aims & Objectives: This study is aimed to determine the factors which are associated with the sexual behavior of high school teenagers in Bukittinggi. Material & Methods: This study was a correlation study with the simple random sampling of 360 adolescent. This research was conducted in February to August 2017. Data analysis uses chi-square. Results: The results of data analysis of factors related to the sexual behavior of high risk are gender (p = 0.000, OR = 0.124), knowledge (p = 0.000, OR = 0.392), attitude (p = 0.000, OR = 2.529), exposure sources information (p = 0.000, OR = 12.405) and peers (p = 0.000, OR = 8.711). Conclusion: Exposure to sources of information (p = 0.000, OR = 8.544) become the dominant factor associated with high-risk sexual behavior of teenagers high schools in the city of Bukittinggi. It is suggested to the schools to provide the student with the extra material about health and sexual behavior in any subjects related to health.